Implementation of Prefabricated Building Systems in Iraq - Khaled, Zeyad S. M. (Al-Nahrain Journal for Engineering Sciences, 2020)
In recent decades, Iraq has witnessed several military operations. This has led to huge damages to the infrastructure of some main cities. The traditional construction methods seem not to be able to fulfill the rapid reconstruction works needed, while prefabricated building systems seem to be promising. This paper aims at evaluating the possibilities of using prefabrication systems for schools building as a pilot study for wider adoption. An extensive literature review was carried out to identify the features of construction prefabrication and its requirements. Then a thorough investigation of the possibilities of adopting this approach in Iraq and the major expected obstacles was carried out. A questionnaire survey has been conducted with (96) stakeholders who have experience in prefabricated building projects. The results showed that the highest rating of benefits went to time and productivity, while the highest rating of obstacles went to lack of government support. Therefore the top proposed action included the adoption of a clear governmental strategy for change. Finally, the respondents agreed that school building is the most suitable type of projects to start with.